The Small GTPase MoSec4 Is Involved in Vegetative Development and Pathogenicity by Regulating the Extracellular Protein Secretion in Magnaporthe oryzae - Zheng, Huakun; Chen, Simiao; Chen, Xiaofeng; Liu, Shuyan; Dang, Xie; Yang, Chengdong; Giraldo, Martha C.; Oliveira-Garcia, Ely; Zhou, Jie; Wang, Zonghua; Valent, Barbara (Frontiers in Plant Science, 2016)
The Rab GTPase proteins play important roles in the membrane trafficking, and consequently protein secretion and development of eukaryotic organisms. However, little is known about the function of Rab GTPases in Magnaporthe oryzae. To further explore the function of Rab GTPases, we deleted the ortholog of the yeast Sec4p protein in M. oryzae, namely MoSEC4. The Mosec4 mutant is defective in polarized growth and conidiation, and it displays decreased appressorium turgor pressure and attenuated pathogenicity. Notably, the biotrophic invasive hyphae produced in rice cells are more bulbous and compressed in the Mosec4 mutant. Further studies showed that deletion of the MoSEC4 gene resulted in decreased secretion of extracellular enzymes and mislocalization of the cytoplasmic effector PWL2-mCherry-NLS. In accordance with its role in secretion, the GFP-MoSec4 fusion protein mainly accumulates at tips of growing vegetative hyphae. Our results suggest that the MoSec4 protein plays important roles in the secretion of extracellular proteins and consequently hyphal development and pathogenicity in the rice blast fungus.